Pengaruh Isolasi Cangkang Telur Ayam Ras Petelur Terhadap Kadar Abu - Rico Arianto; Siti Nani Nurbaeti; Fajar Nugraha; Inarah Fajriaty; Hadi Kurniawan; Adnan Pramudio (State University of Gorontalo, 2022)
Eggshell powder for laying hens contains calcium carbonate CaCO3 (98%) and calcium (28%), efficacious as an antiseptic, antibacterial, and the development of the mineral apatite in the formation of bones and teeth. Eggshell powder is an organic waste that has the potential to be used as a supplement material for calcium sources for humans. However, the content of eggshells consists of inorganic compounds that produce ash. Eggshells as a supplement material must meet quality and safety standards, but this has never been done. Therefore, in this study, an ash content test was carried out with the aim of knowing the inorganic content in the isolation of eggshells of laying hens. Eggshells were isolated by demineralization and deproteination processes. The test results showed that the ash content in the eggshells of laying hens was 95.13%, while in the isolation results the ash content was 96.13%.